Milk-related performances of Murciano-Granadina goats reared in Italy compared to cosmopolitan breeds - Silvia Magro; Angela Costa; Massimo De Marchi; Carmen L. Manuelian (Italian Journal of Animal Science, 2022)
The Murciano-Granadina (MG) goat breed was introduced in 2016 in northern Italy and it has become the third most widespread breed after Saanen (SA) and Alpine (AL). The study aimed to compare milk yield and composition of MG with SA and AL reared under the same farming system. A total of 11,682 milk test-day records from 1947 goats reared in 7 single- and 7 multi-breeds herds were evaluated. All breeds included out off-season kiddings: MG is a permanent polyestric breed whereas specific strategies are commonly adopted to induce oestrus across the year in SA and AL. The mixed model included breed, parity, stage of lactation, kidding season and first-order interactions as fixed effects; goat, herd‐test‐date and residual were random effects. All the effects were significant in explaining the variability of the traits (p < 0.01). The MG yielded 0.93 and 0.50 kg/d less milk (p≤0.05) than SA and AL, respectively, and showed the greatest fat, protein, casein and lactose content and the lowest SCS (p≤0.05). Oppositely to SA, the fat-to-protein ratio (F/P) of MG was always ≥1.00 regardless of lactation stage, parity and kidding season. In conclusion, MG can yield high-quality milk despite being less productive than SA and AL. Moreover, this recently introduced breed, whose reproductive behaviour is less sensitive to season compared to SA and AL, performs efficiently under the Veneto region farming system and can be a genetic resource of interest for the current Italian context.Highlights Milk composition differed among all three breeds: Murciano-Granadina (MG) milk had the greatest lactose and fat content and the lowest SCS. MG goats milk was characterised by greater protein and casein content than Saanen (SA) and was similar to Alpine (AL). The fat-to-protein ratio (F/P) was always >1.00 in MG, while in SA was usually <1.00.